Functional characteristics of Th1, Th17, and ex-Th17 cells in EAE revealed by intravital two-photon microscopy - Loos, Julia (J Neuroinflammation, 2020)
BACKGROUND: T helper (Th) 17 cells are a highly plastic subset of T cells, which in the context of neuroinflammation, are able to acquire pathogenic features originally attributed to Th1 cells (resulting in so called ex-Th17 cells). Thus, a strict separation between the two T cell subsets in the context of experimental autoimmune encephalomyelitis (EAE) is difficult. High variability in culture and EAE induction protocols contributed to previous conflicting results concerning the differential contribution of Th1 and Th17 cells in EAE. Here, we systematically evaluate the role of different T cell differentiation and transfer protocols for EAE disease development and investigate the functional dynamics of encephalitogenic T cells directly within the inflamed central nervous system (CNS) tissue. METHODS: We compiled the currently used EAE induction protocols reported in literature and investigated the influence of the different Th1 and Th17 differentiation protocols as well as EAE induction protocols on the EAE disease course. Moreover, we assessed the cytokine profile and functional dynamics of both encephalitogenic Th1 and Th17 cells in the inflamed CNS using flow cytometry and intravital two-photon laser scanning microscopy. Lastly, we used astrocyte culture and adoptive transfer EAE to evaluate the impact of Th1 and Th17 cells on astrocyte adhesion molecule expression in vitro and in vivo. RESULTS: We show that EAE courses are highly dependent on in vitro differentiation and transfer protocols. Moreover, using genetically encoded reporter mice (B6.IL17A-EGFP.acRFP x 2d2/2d2.RFP), we show that the motility of interferon (IFN)γ-producing ex-Th17 cells more closely resembles Th1 cells than Th17 cells in transfer EAE. Mechanistically, IFNγ-producing Th1 cells selectively induce the expression of cellular adhesion molecules I-CAM1 while Th1 as well as ex-Th17 induce V-CAM1 on astrocytes. CONCLUSIONS: The behavior of ex-Th17 cells in EAE lesions in vivo resembles Th1 rather than Th17 cells, underlining that their change in cytokine production is associated with functional phenotype alterations of these cells. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12974-020-02021-x.